A study on the characteristics of the reef flat bottom and its potential relationship on the size-structure and fine-scale distribution of protoreaster nodosus (Linnaeus, 1758) in Talim Bay, Lian, Batangas - Olin, John Anthony V. (Animo Repository, 2024)
Protoreaster nodosus (Linnaeus, 1758), also known as the chocolate chip starfish, is one of the most common species of starfish in the Indo-Pacific region; however, little is known about their biology and ecology. An observational field study on the accessible areas on the reef flat of Talim Bay, Lian, Batangas was conducted to have an in-depth examination of the potential relationship of the size-structure, distribution, and dispersion to the characteristics of the reef flat bottom. Using a modified version of the Point Center Quarter Method (mPCQM) sampling, the following parameters were measured and recorded: diameter of the starfish, distance of the starfish from a pre-generated random point, depth, diameter of sediment samples, seagrass species present, and other organisms present in the sampling area. These parameters were used to describe the samples and to analyze the possible correlation among the variables. It was found that, on average, the diameter of the samples is 14.7 cm which indicates adulthood. In terms of distribution, an average of only 0.01 starfish/m2 was recorded — comparably lower than those of published studies. Furthermore, the IE values less than 1.27 indicates that P. nodosus species are distributed regularly or uniformly. The clusters and sub-clusters from the classical clustering analysis show potential patterns among the parameters suggesting a direct relationship exists between sediment size and diameter. Moreover, the correlation analysis showed that the seagrass species, Cymodocea spp. and Thalassia hemprichii, have the highest positive correlation coefficient in relation to the size structure of the starfish. This may be due to the the seagrass areas serving as nursery grounds, feeding grounds, and also as refuge from the predators for the smaller (younger) starfish. These would still require further research. To conclude, P. nodosus are observed to have a preference of different sediment sizes and certain species of seagrass depending on their growth stage. For future studies, a prolonged data collection with greater sample and wider sampling area, examination of other abiotic factors such as atmospheric condition, temperature, etc., and a manipulative study to observe their behavior and interaction towards one another are recommended.